Pastoral animators" beliefs and attitudes towards women"s diaconate in the Philippines - Brazal, Agnes M. (HTS teologiese studies, 2025)
The Synthesis Report of the Synod on Synodality (2023) emphasised valuing women’s active roles in the church and continuing theological and pastoral research on women’s access to the diaconate. This research explored Filipino Catholic pastoral animators’ views on women’s ordination to the permanent diaconate. It hopes to provide episcopal leaders in the third-largest Catholic country in the world with an insight into where the pastoral animators stand regarding the issue and, more broadly, on how the respondents view women’s leadership roles. It addresses a geographical and methodological gap, as the first in-depth empirical investigation on the issue in the country. A survey (n = 415) was conducted using snowball sampling. The findings revealed that a vast majority support women’s diaconate, because women and men equally received the ‘variety of gifts of the Spirit’ in baptism (74.6%), and that the reality is women are already performing diaconal tasks (73.9%). There was also huge support (69.0%) for qualified women to be allowed to preach in Mass. A lesser percentage (41.0%) endorsed women’s ordination to the permanent diaconate; the average mean score indicates a ‘neither agree nor disagree’ stance, which does not align with recent surveys showing Filipino’s positive view of women’s leadership in business and politics. The study concludes that the topic of women’s diaconate holds importance in the Philippine context, receiving widespread endorsement despite the mixed support for women’s ordination to the ministry. It equips the church with a valuable perspective on the requisite pastoral education and the misconceptions that must be addressed, in light of the equal dignity and capability of women and men, and the need for women deacons because of the shortage of priests. Contribution: This article addresses a geographical and methodological gap in the study of Catholic attitudes towards women’s ordination to the diaconate in the Philippine context.